BIG DATA – THE NEW CURRENCY OF THE DATA WORLD - Sultanova Lola Sharafovna (Journals Park Publishing, 2023)
The article discusses approaches to understanding кwhy big data is changing the business world and how companies can benefit from it.
Keywords: Big data analytics, business process, structured data, social media data usage, efficientая dataprocessingand analysis.